ErbB deletion effect on pulmonary intracellular surfactant distribution - Nolting, Veronika; Dammann, Christiane E.L.; Hönzke, Katja; Schmiedl, Andreas (Experimental lung research, 2024)
Alveolar epithelial type II cells (AEII) synthesize, store, and recycle surfactant. Lipids and primarily hydrophobic surfactant proteins (SPs) are stored in lamellar bodies (Lbs) while the hydrophilic SPs and the precursors of hydrophobic SPs are stored in multivesicular bodies (mvb). ErbB4-receptor and its ligand neuregulin (NRG) are important regulators of fetal lung development and fetal surfactant synthesis. ErbB4 deletion leads predominantly to an alveolar simplification. We hypothesized that ErbB4 deletion affects the ultrastructure of AEII, specifically Lb and the intracellular distribution of the immunomodulating hydrophilic SP-A and the hydrophobic SP-B. Using a HER4 transgenic cardiac rescue mouse model, AEII were characterized stereologically in lungs of juvenile transgenic HER4 and HER4 mice. The ultrastructure of Lb and the intracellular distribution of SPs were evaluated by immune electron microscopy. A preferential nonrandom labeling of a compartment for SP is present, if the relative labeling index (RLI) > 1and the chi-quadrat test is significant. HER4 deletion had no significant effects on size of AEII and volume fractions of subcellular organelles as well as on the volume weighted mean volume of Lb in HER4 when compared to HER4 mice. The cytoplasm was preferentially labeled for SP-A in the AEII of both genotypes. Lbs were preferential labeled for SP-A in the AEII of HER4 , but not in the AEII of HER4 mice. SP-B was preferentially distributed over Lbs in AEII independent of the genotype, however, the evaluated RLI was significantly higher in HER4 mice. HER4 deletion does not affect the ultrastructure of AEII and influence the distribution of SP-A and SP-B only moderately. Responsible for this could be compensatory mechanisms caused by the redundancy of ErbB receptors.